High-amylose wheat tortillas with reduced in vitro digestion and enhanced resistant starch content. (April 2023) - Li, Caili; Dhital, Sushil; Gidley, Michael J.
Abstract: Increased nutritional functionality in bread and noodles have been reported with the incorporation of high amylose wheat flour (HAWF). Here, we broaden the application of HAWF and report structure-function-nutrition relationships for tortillas prepared with 50% and 100% incorporation of HAWF. The breaking force and extensibility of the HAWF tortillas were lower than controls resulting from incompletely gelatinized high-amylose wheat starch (HAWS). The digestion degree of tortillas was significantly reduced by increase of amylose content due to HAWS structural features and enzyme hindrance effects of greater protein content, with resistant starch (RS) content increasing from ∼3% in control (32% amylose) to ∼12% in tortillas with 71% amylose and ∼23% in tortillas with 84% amylose. In addition, tortillas showed lower starch digestion and higher RS than loaf bread or noodle counterparts. This demonstrates that wheat food in-vitro enzyme hydrolysis is not only a function of starch structure, but also the local density of the microstructure formed during food processing. Graphical abstract: Image 1 Highlights: High amylose wheat tortillas were less extensible and weaker than regular wheat, but similar at 50% inclusion. Resistant starch contents were up to 23% for high amylose compared with 3% for regular tortillas. RS contents higher than for either bread or noodles from the same high amylose wheat flours. Amylase resistance and RS content depends on both amylose content and food microstructure.